The effect of weather factors on the efficiency of macro- and microfertilizers for the red clover cultivation in the conditions of the Kostroma region - G. V. Popova; F. F. Puzdrya; A. V. Bazhenkov; S. A. Kruglova; T. M. Morozova (Зерновое хозяйство России)
Strengthening the forage base is an important task for the successful development of animal husbandry in the Kostroma region, and the main role in this belongs to red clover. The purpose the current study was to identify the dependence of the productivity of clover green mass on the type and dose of top dressing, when using sparing doses of fertilizers and environmentally friendly types of processing. The study was carried out on the basis of the Kostroma Research Institute of Agriculture in 2020–2022. The two-factor trial consisted of 15 options (three backgrounds – Control, Ozone and “Aquamix”, and 5 options for different doses of top dressing) in three sequences, the area of one plot was 6 m2. There was taken the clover variety ‘Soligalichesky mestny’ as the most adapted to the soil and climatic conditions of the region. During the study, there was found a dependence of the efficiency of the applied fertilizers on weather factors during the vegetation period. Thus, under favorable climatic conditions, the complex “Aquamix” was effective both in pre-sowing treatment and in the form of foliar top dressing. In the variants with its use, there was obtained a significant improvement of green mass productivity and general productivity indicators. The P30K30 dose was the most effective among all mineral top dressings. When increasing the dose and introducing nitrogen (N30P45K90) in the top dressing, productivity and quality of the green mass decreased mainly due to grass lodging. During the unfavorable vegetation period (summer drought), microelements did not affect forage mass productivity and quality. Only top dressing with mineral fertilizers was effective, and the best result was obtained with a higher dose and the full composition of top dressing (N30P45K90). Seed ozonation was effective under all weather conditions. The best result in a favorable year was obtained in the variant Ozone + P30K30 (+43.8 t/ha of green mass, or 153 %), in an unfavorable year it was Ozone + N30P45K90 (+16.1 t/ha, or 111 %). The dose of mineral top dressing ought to be adjusted depending on the weather conditions of a particular vegetation period.